Familia, infancia, adolescencia y violencia - Signorini, Hebe (My University, 2015)
The domestic violence is one of the some modalities of violence expression that the humanity practises against its children and adolescents, being this phenomenon also is associated with the historical, social, cultural context and politician where if inserts not being able to be extended understood as an isolated fact. It is of great importance that the confrontation of the violence against children and adolescents, either come back not only to the attendance of the victims, but that also takes care of its families and that beyond the attendance of the victims, it may have a prevention of the violence that if it installs in the Brazilian homes.
Keywords: Violencia familiar - Brasil; Infancia; Adolescencia